(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The dynamic development of agrarian markets and the latest technologies with the application of developments in the theory and practice of logistics management of agricultural enterprises can become one of the most important factors for increasing the competitiveness of agricultural business and effectively meeting the needs of consumers. Increasing the efficiency of agricultural production is impossible without the use of highly skilled management. Against the background of the described situation, the problem is the choice of efficient and effective approaches to logistics management of the agricultural enterprise and the selection of effective logistics tools. The article deals with approaches to management in general, and approaches to logistics management in particular with its inherent tools in the activity of agricultural enterprises. The development and effective functioning of agricultural enterprises against the backdrop of an unstable economic situation in the country is possible with the use of successful management approaches, using existing developments in the theory and practice of logistics management. Implementation and application of innovative approaches and concepts in the field of logistics will provide agricultural enterprises with high competitive advantages in agribusiness and successful access to foreign agro-markets. However, practical implementation of changes is not possible without the use of methods and tools of logistic management, taking into account the specifics of the activities of agricultural enterprises, which in turn is the basis of an effective management mechanism. The application of various combinations and approaches to managing logistics tools will allow agricultural enterprises to develop, to increase their capacities, and to maintain leadership in the agrarian market of the country and beyond.